Stress-induced Changes in the S-palmitoylation and S-nitrosylation of Synaptic Proteins - Zareba-Koziol, Monika (Mol Cell Proteomics, 2019)
The precise regulation of synaptic integrity is critical for neuronal network connectivity and proper brain function. Essential aspects of the activity and localization of synaptic proteins are regulated by posttranslational modifications. S-palmitoylation is a reversible covalent modification of the cysteine with palmitate. It modulates affinity of the protein for cell membranes and membranous compartments. Intracellular palmitoylation dynamics are regulated by crosstalk with other posttranslational modifications, such as S-nitrosylation. S-nitrosylation is a covalent modification of cysteine thiol by nitric oxide and can modulate protein functions. Therefore, simultaneous identification of endogenous site-specific proteomes of both cysteine modifications under certain biological conditions offers new insights into the regulation of functional pathways. Still unclear, however, are the ways in which this crosstalk is affected in brain pathology, such as stress-related disorders. Using a newly developed mass spectrometry-based approach Palmitoylation And Nitrosylation Interplay Monitoring (PANIMoni), we analyzed the endogenous S-palmitoylation and S-nitrosylation of postsynaptic density proteins at the level of specific single cysteine in a mouse model of chronic stress. Among a total of 813 S-PALM and 620 S-NO cysteine sites that were characterized on 465 and 360 proteins, respectively, we sought to identify those that were differentially affected by stress. Our data show involvement of S-palmitoylation and S-nitrosylation crosstalk in the regulation of 122 proteins including receptors, scaffolding proteins, regulatory proteins and cytoskeletal components. Our results suggest that atypical crosstalk between the S-palmitoylation and S-nitrosylation interplay of proteins involved in synaptic transmission, protein localization and regulation of synaptic plasticity might be one of the main events associated with chronic stress disorder, leading to destabilization in synaptic networks.